Predicting Academic Achievement Based on Self-Regulated Learning and Family Cultural Capital in High School Students in Tehran - Sooki, Sepide; Bagheri, Nasrin; Babakhani, Narges; Mojtabaee, Mina (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The objective of this study was to predict academic achievement based on self-regulated learning and family cultural capital in high school students in Tehran.Methods and Materials: The study employed a quantitative, descriptive-correlational survey design, with data collected from 300 high school students in Tehran using multi-stage cluster sampling. Data collection tools included Bourdieu’s Cultural Capital Questionnaire (1973), Bouffard et al.’s Self-Regulated Learning Questionnaire (2015), and an Academic Achievement Questionnaire adapted from Pham and Taylor’s research (1990). Data analysis was conducted using SPSS22, employing descriptive statistics, Pearson correlation, multiple regression, and multivariate regression analyses.Findings: The findings revealed that self-regulated learning (B = 0.55, p < .001) and family cultural capital (B = 0.40, p < .001), significantly predicted academic achievement, with self-regulated learning being the strongest predictor.Conclusion: In conclusion, self-regulated learning and family cultural capital play critical roles in predicting academic achievement among high school students. These findings emphasize the importance of fostering self-regulation strategies, enriching family cultural capital, and promoting positive learning attitudes to enhance academic performance.